Revolutionizing full-mouth rehabilitation: digital integration of Hobo’s philosophy with CAD/CAM multilayered zirconia crowns: a case report - Mahajan, Mohan C.; K. Jurel, Sunit; Chand, Pooran; Boricha, Aashita; Kaundal, Sonali (International Journal of Research in Medical Sciences, 2025)
Severe occlusal wear disrupts function, aesthetics, and occlusal harmony. Hobo’s twin-stage philosophy offers a structured approach to full-mouth rehabilitation. Integrating this with CAD/CAM technology enhances precision and clinical outcomes. A 28-year-old male with generalized tooth wear and compromised function underwent full-mouth rehabilitation. Vertical dimension was increased by 2 mm following occlusal splint evaluation. Hobo’s twin-stage technique was applied using a semi-adjustable articulator. Digital impressions and CAD/CAM workflows facilitated the fabrication of multilayered zirconia crowns.The patient showed excellent adaptation to the increased vertical dimension. Functional occlusion with canine guidance and posterior disclusion was achieved. The final restorations demonstrated precise fit, esthetics, and occlusal stability, with high patient satisfaction. Digital integration of Hobo’s twin-stage protocol with CAD/CAM zirconia restorations offers a predictable, efficient, and esthetically superior solution for managing severe tooth wear.